2015
DOI: 10.1007/s11010-015-2334-1
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1224-5p acts as a tumor suppressor by targeting CREB1 in malignant gliomas

Abstract: The dysregulation of miR-1224-5p has been reported in several human cancers. However, the expression and function of miR-1224-5p in glioma remains unknown. The aim of our study was to investigate the effect of miR-1224-5p on glioma cells and to determine its functional signaling mediators. Using 198 glioma samples within the Chinese Glioma Genome Atlas expression dataset, we demonstrated that miR-1224-5p expression is decreased in high-grade gliomas when compared with low-grade gliomas. Differential miR-1224-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 40 publications
4
41
0
Order By: Relevance
“…The mechanism by which CREB regulates glioblastoma tumor cell proliferation involves activities downstream from both the MAPK and PI3K pathways that then modulate the expression of three key cell cycle factors, cyclin B1, cyclin D1 and PCNA [32]. It has been shown that miR-1224-5p and miR-200b act as tumor suppressors by targeting CREB in malignant gliomas [33, 34]. Herein, we demonstrated that CREB is a direct target of miR-433-3p in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which CREB regulates glioblastoma tumor cell proliferation involves activities downstream from both the MAPK and PI3K pathways that then modulate the expression of three key cell cycle factors, cyclin B1, cyclin D1 and PCNA [32]. It has been shown that miR-1224-5p and miR-200b act as tumor suppressors by targeting CREB in malignant gliomas [33, 34]. Herein, we demonstrated that CREB is a direct target of miR-433-3p in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nymark et al reported that miR-1224-5p is remarkably decreased in asbestos-related lung cancer (16). In addition, miR-1224-5p acts as a tumor suppressor to repress cell proliferation and invasion and promote apoptosis by downregulating the expression of CREB1 in malignant gliomas (17). Furthermore, the up-regulation of miR-1224-5p inhibits the proliferation and invasion and promotes the apoptosis of keloid cells via the TGF-β1/Smad3 signaling pathway (18).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 10 miRNAs were negatively correlated with TACC3 expression and qualified as having a binding site within the TACC3 mRNA 3′ untraslational region. Some of these miRNAs, such as miR-1224-5p [27], miR-30e-3p [28], miR-488-3p [29], miR-491-5p [30], miR-940 [31] and miR-885-3p [32], are proven as tumor suppressors for various cancers. In the CGGA miRNA dataset, these TACC3 negatively associated miRNAs were significantly downregulated in high grade glioma (except for miR-330-3p, p = 0.4164) (Figure S5).…”
Section: Resultsmentioning
confidence: 99%